Highly charged ion (HCI) clocks: Frontier candidates for testing variation of fine-structure constant - Yu, Yan-Mei; Sahoo, B. K.; Suo, Bing-Bing (Frontiers in Physics, 2023)
Attempts are made to unify gravity with the other three fundamental forces of nature. As suggested by higher dimensional models, this unification may require space and time variation of some of the dimensionless fundamental constants. In this scenario, probing temporal variation of the electromagnetic fine structure constant ($α= \frac{e^2} {\hbar c}$) in a low energy regime at the cosmological time scale is of immense interest. Atomic clocks are ideal candidates for probing $α$ variation because their transition frequencies are measured with ultra-high precision. Since atomic transition frequency is a function of $α$, measurement of a clock frequency at different temporal and spatial locations can yield signatures to ascertain variation of $α$. Highly charged ions (HCIs) are very sensitive to variation of $α$ and are least affected by external perturbations, making them excellent platforms for searching for temporal variation of $α$. In this work, we overview HCIs suitable for building atomic clocks because of their spectroscopic features and sensitivity to variation of $α$. The selection of HCI clock candidates is outlined based on two general rules -- by analyzing trends in fine structure splitting and level-crossing patterns along a series of isoelectronic atomic systems of the periodic table. Two variants of relativistic many-body methods in the configuration interaction and coupled-cluster theory frameworks are employed to determine the properties of HCIs proposed for atomic clocks. These methods treat electronic correlation and relativistic effects under the frame of the Dirac-Coulomb Hamiltonian rigorously, while other higher-order relativistic effects are included approximately. Typical systematic effects of the HCI clock frequency measurements are discussed using the calculated atomic properties. This review will help understand limits and potentials of the proposed HCIs as the prospective atomic clock candidates and guide future HCI clock experiments.